Proteomics-driven screening of artemisinin-based combination ratios and mechanistic insights into Plasmodium berghei infection in mice - Hao, Liyu; Sun, Jianhui; Li, Jianliang; Li, Zongyuan; Yu, Zeyue; Huang, Hanhui; Liu, Guimin; Shen, Zhenru; Huo, Hairu; Yuan, Qili; Li, Hongmei; Huang, Luqi (Frontiers in Immunology, 2025)
IntroductionMalaria, a life-threatening mosquito-borne disease caused by Plasmodium falciparum, poses a substantial health burden on tropical and subtropical regions. Artemisinin, a sesquiterpene lactone isolated from Artemisia annua L., and its derivatives were initially used as monotherapies for malaria treatment. However, limitations such as short pharmacokinetic half-life and emerging drug resistance have driven the widespread adoption of artemisinin-based combination therapies (ACTs) as first-line interventions. A. annua contains other bioactive compounds such as arteannuin B, artemisinic acid, and scopoletin that exhibit distinct pharmacological properties. In this study, we aimed to devise a new strategy for treatment of malaria to overcome artemisinin resistance in Plasmodium species.MethodsWe systematically screened antimalarial compound ratios using murine malaria models and optimized a formula comprising arteannuin B, artemisinic acid, and scopoletin. Through integrated proteomic profiling and western blot validation, we elucidated the immunomodulatory mechanisms underlying the antimalarial efficacy of this combination.ResultsSpecifically, the formula strengthened host defense by modulating phagocytic activity in splenic macrophages, dendritic cells, and natural killer cells via Fcγ receptor-mediated pathways.DiscussionThese findings provide mechanistic insights into artemisinin-associated immune potentiation. Moreover, we have proposed a novel ACT strategy targeting host-parasite interactions, offering a promising approach to circumvent emerging artemisinin resistance in Plasmodium species.